2012
DOI: 10.1007/s10295-012-1131-z
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes of corn stover lignin during acid pretreatment

Abstract: In this study, raw corn stover was subjected to dilute acid pretreatments over a range of severities under conditions similar to those identified by the National Renewable Energy Laboratory (NREL) in their techno-economic analysis of biochemical conversion of corn stover to ethanol. The pretreated corn stover then underwent enzymatic hydrolysis with yields above 70 % at moderate enzyme loading conditions. The enzyme exhausted lignin residues were characterized by ³¹P NMR spectroscopy and functional moieties qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 29 publications
1
46
0
Order By: Relevance
“…The higher S/G ratios of the corn stover lignin and the rice straw lignin (see Table 4) also caused reactive thermolysis because of the additional chances from one more -OCH 3 group of a syringyl unit [20]. On the other hand, the ReLignin had a much higher temperature range for primary pyrolysis than even the Kraft lignin because acid pretreatment might release more syringyl units from lignin depolymerization and, thus, could induce more condensed phenolic units with stronger thermal stability [31].…”
Section: Thermal Degradation Of Lignin Componentsmentioning
confidence: 96%
See 1 more Smart Citation
“…The higher S/G ratios of the corn stover lignin and the rice straw lignin (see Table 4) also caused reactive thermolysis because of the additional chances from one more -OCH 3 group of a syringyl unit [20]. On the other hand, the ReLignin had a much higher temperature range for primary pyrolysis than even the Kraft lignin because acid pretreatment might release more syringyl units from lignin depolymerization and, thus, could induce more condensed phenolic units with stronger thermal stability [31].…”
Section: Thermal Degradation Of Lignin Componentsmentioning
confidence: 96%
“…The total number of phenolic hydroxyl groups in the lignin complexes would also be increased by the acid pretreatment [31]. However, autohydrolysis (hot water only pretreatment) of lignin with increasing temperatures resulted in a decrease in molecular weight [35].…”
Section: Phenolic Aromatic Compounds From Pyrolysis Of Different Lignmentioning
confidence: 98%
“…For example, high severity dilute acid pretreatment is thought to catalyze aryl-ether (C-O) bond cleavage in lignin and promote recondensation of C-C linkages, likely rendering lignin more recalcitrant [135,136]. Thus, the nature of the upstream pretreatment chemistry intended to (in some cases) remove hemicellulose, redistribute lignin, and render biomass more digestible by enzymes should be considered in light of the intended downstream lignin conversion process.…”
Section: Lignin Utilization: Technical Contextmentioning
confidence: 99%
“…Evidence has also suggested that syringyl units were more readily degraded than guaiacyl units under dilute acid pretreatment conditions, resulting in a lower S/G ratio in lignin in pretreated biomass [9]. In addition, DAP results in the formation of new phenolic groups due in part to the cleavage of β-O-4 aryl ether bonds [85]. Other structural changes such as a decrease in methoxyl group content, hydrolysis of acetyl groups, and cinnamaldehyde units are also observed during dilute acid pretreatment [9].…”
Section: Dilute Acid Pretreatmentmentioning
confidence: 96%